An Assessment of the Anaerobic Vial of Paired NR 6A and NR 7N Bactec Blood Cultures. (1994) - Forward, Kevin R; Kerr, Elizabeth; Dalton, Maurice
Abstract : Objective: To determine the number of obligate anaerobes recovered in anaerobic blood culture vials and to determine if their recovery had a significant impact on patient care. Design: Retrospective review. Setting: Tertiary care teaching hospital. Main Results: Six thousand nine hundred and five pairs of Bactec blood cultures were submitted (each set consisted of one 6A and one 7N vial). Of these, 690 sets were culture-positive in at least one of the vials (10% of pairs). Both vials were positive in 406 (58.8%). The aerobic vial alone was positive in 176 (25.5%) and the anaerobic vial alone was positive in 107 (15.5%). Of these, most were facultative anaerobes; however, 20 blood culture sets from 18 patients were positive for obligate anaerobes. In five of the 18, the isolate was judged to be a contaminant. In 11 of 13 patients, the clinically significant obligate anaerobic bacteremia might have been predicted on clinical grounds, and in eight patients, empirical antianaerobic antibiotics had been started before the results of blood cultures were known. Conclusions: Clinical laboratories should carefully examine the use of the routine anaerobic blood culture and consider its replacement with larger volume aerobic blood culture vials.